PENGANTIN SEMARANGAN: TRADISI YANG MESTI DI-URI-URI - Mytha Candria (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2022)
Semarang, the capital city of Central Java Province, has its own traditional style of wedding ceremony, the so called Pengantin Semarang or Pengantin Semarangan. Literally meaning Semarang wedding ceremony, Pengantin Semarangan is a combination of four traditional wedding styles, i.e. those of Javanese, Malay, Chinese, and Arabic, and thus symbolizes peace, unity, tolerance, and harmony among these majority ethnic groups living side by side in Semarang for thousands of years. Unfortunately, this valuable wedding ceremony is continously diminishing, as the people of Semarang themselves belittle their ancestor tradition. Unless a serious effort is made to preserve the tradition, the grandeur of Pengantin Semarangan may one day become a mere story